The Concept of Grundnorm in the Customary Law System: Reconciliation of Hans Kelsen's Pure Legal Theory with Indonesian Legal Pluralism - Anam, Ahmad Gautsul; Paradina, Wanda (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Indonesia adheres to a pluralistic legal system, with state law, customary law, and religious law applying simultaneously. This study analyzes the relevance of Hans Kelsen's grundnorm concept in understanding the hierarchy and validity of the Indonesian customary law system. The focus of the research includes: (1) how the grundnorm concept can be applied in the context of Indonesian customary law, (2) how to reconcile Kelsen's pure legal theory with the reality of legal pluralism in Indonesia, and (3) the theoretical and practical implications of the application of the grundnorm concept to the existence of customary law. This study uses a juridical-normative method with a conceptual and philosophical approach. Secondary data were obtained from legal literature, scientific journals, and related laws and regulations. The results of the study indicate that: Kelsen's grundnorm concept can be adapted in the customary law system through the identification of basic norms derived from the philosophical values of indigenous communities; there is a possibility of reconciliation between the pure legal theory and legal pluralism through a multi-grundnorm approach that recognizes the existence of more than one basic norm in the national legal system; and the application of the grundnorm concept provides theoretical legitimacy for the existence of customary law as an autonomous legal subsystem but remains within the framework of the unity of the Indonesian national legal system.